Phosphorus sulfide composition for sulfide-based inorganic solid electrolyte materials

The use of a phosphorus sulfide composition with specific content ranges and mechanical treatment enhances lithium ion conductivity in sulfide-based inorganic solid electrolyte materials, leading to improved battery performance.

JP7605908B2Active Publication Date: 2024-12-24FURUKAWA COMPANY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023097583
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-02
Filing Date
2023-06-14
Publication Date
2024-12-24
Estimated Expiration
2040-08-18

AI Technical Summary

Technical Problem

Sulfide-based inorganic solid electrolyte materials exhibit inferior lithium ion conductivity compared to conventional electrolytes, necessitating an improvement in this critical property for enhanced performance in lithium ion batteries.

Method used

A phosphorus sulfide composition with specific content ranges of P4S10, P4S9, P4S7, and P4S3 is used to enhance lithium ion conductivity, combined with a mechanical treatment process to produce a sulfide-based inorganic solid electrolyte material.

Benefits of technology

The improved lithium ion conductivity results in better battery characteristics, including higher conductivity and input/output performance in lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605908000002
    Figure 0007605908000002
  • Figure 0007605908000001
    Figure 0007605908000001
Patent Text Reader

Abstract

To provide a phosphorus sulfide composition that can improve the lithium ionic conductivity in the resultant sulfide-based inorganic solid electrolyte material.SOLUTION: Provided is a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, the phosphorus sulfide composition including P4S10 and P4S9. When a total content of P4S10, P4S9, P4S7 and P4S3 in the phosphorus sulfide composition is represented by 100 mass%, a content of P4S10 calculated from a solid 31 P-NMR spectrum is 70 mass% or more and 99 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a phosphorus sulfide composition for use in a sulfide-based inorganic solid electrolyte material. [Background technology]

[0002] Lithium-ion batteries are generally used as power sources for small portable devices such as mobile phones and laptops, etc. Recently, lithium-ion batteries have also begun to be used as power sources for electric vehicles, power storage, and other devices in addition to small portable devices.

[0003] Currently available lithium-ion batteries use electrolytes that contain flammable organic solvents. On the other hand, lithium-ion batteries that use a solid electrolyte to make the battery all-solid-state (hereinafter also referred to as all-solid-state lithium-ion batteries) do not use flammable organic solvents in the battery, which allows for simplified safety devices and is thought to be superior in terms of manufacturing costs and productivity.

[0004] As a solid electrolyte material used for such a solid electrolyte, for example, a sulfide-based inorganic solid electrolyte material is known.

[0005] In Patent Document 1 (JP 2016-27545 A), a peak is observed at 2θ=29.86°±1.00° in X-ray diffraction measurement using CuKα radiation, and Li 2y+3 A sulfide-based solid electrolyte material is described that is characterized by having a composition of PS4 (0.1≦y≦0.175).

[0006] Patent Document 2 (WO 2016 / 067631) describes a method for producing sulfide glass using phosphorus sulfide as a raw material according to the following formula (1). 100×A / B≧37...(1) (Wherein, A is 31In the PNMR spectrum analysis, B indicates the peak area of ​​the peaks appearing in the ranges of 57.2 ppm to 58.3 ppm and 63.0 ppm to 64.5 ppm, and B indicates the total peak area of ​​all peaks measured. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2016-27545 A [Patent Document 2] International Publication No. 2016 / 067631 Summary of the Invention [Problem to be solved by the invention]

[0008] Although sulfide-based inorganic solid electrolyte materials have excellent electrochemical stability and lithium ion conductivity, their lithium ion conductivity is inferior to that of electrolyte solutions. For these reasons, there is a demand for sulfide-based inorganic solid electrolyte materials used in lithium-ion batteries to have electrochemical stability while also exhibiting improved lithium ion conductivity.

[0009] The present invention has been made in view of the above circumstances, and provides a phosphorus sulfide composition capable of improving the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material. [Means for solving the problem]

[0010] The present inventors have conducted extensive research in order to provide a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity. As a result, it has been found that a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity can be produced by using a solid 31 P4S calculated from P-NMR spectrum 10 The present inventors have found that the use of a phosphorus sulfide composition having a content of within a specific range can improve the lithium ion conductivity of the resulting sulfide-based inorganic solid electrolyte material, and have completed the present invention.

[0011] That is, according to the present invention, A phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, comprising: P4S 10 and P4S9, P4S in the phosphorus sulfide composition 10 When the total content of P4S9, P4S7 and P4S3 is 100 mass%, solid 31 The above P4S calculated from the P-NMR spectrum 10 The phosphorus sulfide composition has a content of from 70 mass % to 99 mass %.

[0012] Further, according to the present invention, There is provided a raw material composition for a sulfide-based inorganic solid electrolyte material, comprising the phosphorus sulfide composition and lithium sulfide.

[0013] Further, according to the present invention, There is provided a method for producing a sulfide-based inorganic solid electrolyte material, comprising a step of mechanically treating the raw material composition for the sulfide-based inorganic solid electrolyte material.

[0014] Further, according to the present invention, There is provided a sulfide-based inorganic solid electrolyte material obtained by using the phosphorus sulfide composition as a raw material.

[0015] Further, according to the present invention, A solid electrolyte is provided that includes the sulfide-based inorganic solid electrolyte material.

[0016] Further, according to the present invention, There is provided a solid electrolyte membrane containing the above solid electrolyte as a main component.

[0017] Further, according to the present invention, A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, There is provided a lithium ion battery in which at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material. Effect of the Invention

[0018] According to the present invention, it is possible to provide a phosphorus sulfide composition capable of improving the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material. [Brief description of the drawings]

[0019] [Figure 1] 1 is a cross-sectional view showing an example of the structure of a lithium-ion battery according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given the same reference numerals and the description will be omitted as appropriate. The drawings are schematic diagrams and do not correspond to the actual dimensional ratios. The numerical range "A to B" indicates A or more and B or less unless otherwise specified.

[0021] [Phosphorus sulfide composition] First, the phosphorus sulfide composition according to this embodiment will be described. The phosphorus sulfide composition according to the present embodiment is a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material (hereinafter also referred to as a phosphorus sulfide composition), and is P4S 10 and P4S9, 10 When the total content of P4S9, P4S7 and P4S3 is 100 mass%, the solid 31 P4S calculated from P-NMR spectrum 10 The content is 70% by mass or more and 99% by mass or less, preferably 72% by mass or more, more preferably 75% by mass or more, further preferably 77% by mass or more, and particularly preferably 80% by mass or more. solid 31 P4S calculated from P-NMR spectrum 10The upper limit of the content is not particularly limited, but may be 98 mass % or less, or 95 mass % or less.

[0022] The phosphorus sulfide composition according to this embodiment is P4S 10 When the content is equal to or more than the above lower limit, the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material can be improved. The reason for this is not entirely clear, but the phosphorus sulfide composition according to this embodiment is P4S 10 Since the content of P4S is relatively high, 10 This is thought to be because the content of phosphorus sulfide compounds (P4S9, P4S7, P4S3, etc.) with boiling points equal to or lower than those of phosphorus sulfide polymers (insoluble sulfur) decreases. For the above reasons, since the phosphorus sulfide composition according to the present embodiment contains a relatively small amount of a phosphorus sulfide compound or a phosphorus sulfide polymer having a low boiling point, it is believed that the use of the phosphorus sulfide composition according to the present embodiment can improve the lithium ion conductivity of the resulting sulfide-based inorganic solid electrolyte material. In this embodiment, P4S 10 The phosphorus sulfide composition having the above-mentioned range of content can be obtained, for example, by subjecting a raw material composition of phosphorus sulfide to vacuum heating to thereby obtain a phosphorus sulfide composition having a P4S content of P4S. 10 It is possible to obtain the above-mentioned product by carrying out a process for reducing the amount of phosphorus sulfide compounds (P4S9, P4S7, P4S3, etc.) having a boiling point equal to or lower than that of phosphorus sulfide polymers.

[0023] In the phosphorus sulfide composition according to this embodiment, 31 The content of P4S9 calculated from the P-NMR spectrum is preferably 1% by mass or more and 30% by mass or less. 31 The upper limit of the P4S9 content calculated from the P-NMR spectrum is preferably 28% by mass or less, more preferably 25% by mass or less, even more preferably 23% by mass or less, and particularly preferably 20% by mass or less. solid 31The lower limit of the P4S9 content calculated from the P-NMR spectrum is not particularly limited, but may be 2% by mass or more, or 5% by mass or more.

[0024] solid 31 The P-NMR spectrum can be measured, for example, by the following method. First, a test sample is filled into a 3.2 mm diameter measurement sample tube in a glove box purged with N2 gas, and the tube is rotated at a magic angle (54.7 degrees) relative to the external magnetic field (Magic Angle Spinning: MAS), and measurements are performed under the following conditions. Equipment: JNM-ECA-600 manufactured by JEOL RESONANCE Co., Ltd. Observation frequency: 242.95MHz Pulse width: 90° pulse Pulse waiting time: 2800 seconds Number of times accumulated: 64 Measurement mode: Single pulse method MAS speed: 12kHz Standard substance: (NH4)2HPO4·1.33ppm Test sample 31 Regarding the peaks detected in the P-NMR spectrum, see Reference 1 "Hellmut Eckert, Cheryl S. Liang and Galen D. Stucky: 31 P magic angle spinning NMR of crystalline phosphorous sulfides. Correlation of 31 P chemical shielding tensors with local environments, J. Phys. Chem, 1989, 93, 452-457, and perform waveform separation using a Gaussian function based on the following peak assignments to calculate the integral value of each peak. The integral value of the peak derived from each component is proportional to the number of moles of phosphorus contained. Therefore, the content ratio can be calculated from the obtained integral value and the molecular weight of each component. P4S 10The chemical shifts of P4S1, P4S2, and P4S3 are 40-52 ppm, 52-70 ppm, 80-90 ppm, 90-100 ppm, and 110-115 ppm, respectively, and P4S3, P4S4, and P4S5 are 80-90 ppm and 90-100 ppm, respectively.

[0025] In the phosphorus sulfide composition according to this embodiment, 31 When the P-NMR spectrum is measured, it is preferable that no peaks are observed in the range of 80 ppm to 90 ppm. In other words, it is preferable that no peaks of P4S7 and P4S3 are observed. This makes it possible to determine whether the P4S 10 The proportion of can be increased, and the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material can be further improved.

[0026] The phosphorus sulfide composition according to this embodiment is P4S 10 and P4S9. The P4S in the phosphorus sulfide composition according to this embodiment 10 The total content of P4S and P4S9 is preferably 95% by mass or more, more preferably 97% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more, in order to further improve the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material. 10 The upper limit of the total content of P4S and P4S9 is not particularly limited, but is, for example, 100 mass% or less. 10 Other possible components besides P4S9 include P4S7 and P4S3.

[0027] The phosphorus sulfide composition according to the present embodiment may be in the form of, for example, a powder. Since the production of a sulfide-based inorganic solid electrolyte material described below is generally performed in a dry manner, the production of the sulfide-based inorganic solid electrolyte material becomes easier when the phosphorus sulfide composition according to the present embodiment is in the form of a powder.

[0028] [Method of producing phosphorus sulfide composition] Next, a method for producing the phosphorus sulfide composition according to this embodiment will be described. The method for producing the phosphorus sulfide composition according to the present embodiment is different from the conventional method for producing phosphorus sulfide compositions. 10 The phosphorus sulfide composition having the above-mentioned range of content can be obtained by, for example, subjecting a raw material composition of phosphorus sulfide to vacuum heating to thereby obtain a phosphorus sulfide composition having a P4S content of P4S. 10 This can only be achieved by adopting manufacturing process innovations such as treatments to reduce the amount of phosphorus sulfide compounds (P4S9, P4S7, P4S3, etc.) that have boiling points equal to or lower than that of phosphorus sulfide polymers (insoluble sulfur). However, the method for producing the phosphorus sulfide composition according to this embodiment can employ various specific production conditions, for example, on the premise that the above-mentioned ingenious features in the production process are adopted. The method for producing the phosphorus sulfide composition according to this embodiment will be described in more detail below.

[0029] The method for producing a phosphorus sulfide composition according to this embodiment includes, for example, the following steps (X) and (Y). Step (X): preparing a raw material composition of phosphorus sulfide Step (Y): The raw material composition of phosphorus sulfide is heated in a vacuum, for example, to obtain P4S in the phosphorus sulfide composition. 10 A process to reduce the amount of phosphorus sulfide compounds (P4S9, P4S7, P4S3, etc.) and phosphorus sulfide polymers (insoluble sulfur) having a boiling point equal to or lower than that of

[0030] First, a raw material composition of phosphorus sulfide is prepared. The raw material composition of phosphorus sulfide used as the raw material is not particularly limited, and commercially available diphosphorus pentasulfide (P4S 10 ) may be used as it is, or a raw material composition of phosphorus sulfide obtained by a generally known method for producing diphosphorus pentasulfide may be used.

[0031] Next, the raw material composition of phosphorus sulfide is heated in a vacuum, for example, to remove P4S in the phosphorus sulfide composition. 10The amount of phosphorus sulfide compounds (P4S9, P4S7, P4S3, etc.) and phosphorus sulfide polymers having a boiling point equal to or lower than P4S is reduced. 10 The vacuum heating is continued until the content of falls within the above range. This allows the phosphorus sulfide composition according to the present embodiment to be obtained. Here, when the phosphorus sulfide raw material composition is, for example, vacuum heated, the component that does not evaporate but remains at the bottom of the container is usually the phosphorus sulfide composition according to the present embodiment.

[0032] The conditions such as pressure, heating temperature, and treatment time when the phosphorus sulfide raw material composition is vacuum heated can be appropriately determined depending on the amount of the phosphorus sulfide raw material composition to be treated. The pressure in the vacuum heating device when the phosphorus sulfide raw material composition is vacuum-heated is, for example, −0.01 MPa or less, and preferably −0.07 MPa or less. The heating temperature when the phosphorus sulfide raw material composition is vacuum heated is, for example, 220°C or higher and 500°C or lower, and preferably 250°C or higher and 350°C or lower. The time for vacuum heating the phosphorus sulfide raw material composition is, for example, from 0.5 hours to 24 hours, and preferably from 1 hour to 5 hours.

[0033] [Sulfide-based inorganic solid electrolyte material] Hereinafter, the sulfide-based inorganic solid electrolyte material according to this embodiment will be described. The sulfide-based inorganic solid electrolyte material according to this embodiment can be obtained by using the phosphorus sulfide composition according to this embodiment as a raw material.

[0034] The sulfide-based inorganic solid electrolyte material according to this embodiment preferably contains Li, P and S as constituent elements from the viewpoint of further improving electrochemical stability, stability in moisture and air, ease of handling, and the like. In addition, in the sulfide-based inorganic solid electrolyte material according to this embodiment, from the viewpoint of further improving lithium ion conductivity, electrochemical stability, stability in moisture and air, and ease of handling, the molar ratio Li / P of the Li content to the P content in the sulfide-based inorganic solid electrolyte material is preferably 1.0 or more and 5.0 or less, more preferably 2.0 or more and 4.0 or less, even more preferably 2.5 or more and 3.8 or less, even more preferably 2.8 or more and 3.6 or less, even more preferably 3.0 or more and 3.5 or less, even more preferably 3.1 or more and 3.4 or less, particularly preferably 3.1 or more and 3.3 or less, and the molar ratio S / P of the S content to the P content is preferably 2.0 or more and 6.0 or less, more preferably 3.0 or more and 5.0 or less, even more preferably 3.5 or more and 4.5 or less, even more preferably 3.8 or more and 4.2 or less, even more preferably 3.9 or more and 4.1 or less, particularly preferably 4.0. Here, the contents of Li, P and S in the sulfide-based inorganic solid electrolyte material according to this embodiment can be determined by, for example, ICP emission spectrometry or X-ray analysis.

[0035] In the sulfide-based inorganic solid electrolyte material according to this embodiment, the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material is preferably 0.5×10 -3 S cm -1 More preferably, 0.6×10 -3 S cm -1 More preferably, 0.8×10 -3 S cm -1 More preferably, 1.0×10 -3 S cm -1 That's all. When the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material according to the present embodiment is equal to or higher than the lower limit, a lithium ion battery having better battery characteristics can be obtained. Furthermore, when such a sulfide-based inorganic solid electrolyte material is used, a lithium ion battery having better input / output characteristics can be obtained.

[0036] The sulfide-based inorganic solid electrolyte material according to this embodiment may be in the form of particles, for example. The particulate sulfide-based inorganic solid electrolyte material according to the present embodiment is not particularly limited, but may have an average particle diameter d 50 However, the thickness is preferably 1 μm or more and 100 μm or less, more preferably 3 μm or more and 80 μm or less, and further preferably 5 μm or more and 60 μm or less. Average particle size d of sulfide-based inorganic solid electrolyte material 50 By setting the value within the above range, it is possible to maintain good handling properties and further improve the lithium ion conductivity.

[0037] The sulfide-based inorganic solid electrolyte material according to this embodiment is preferably excellent in electrochemical stability. Here, electrochemical stability refers to, for example, the property of being difficult to be oxidized and reduced in a wide voltage range. More specifically, in the sulfide-based inorganic solid electrolyte material according to this embodiment, the maximum value of the oxidative decomposition current of the sulfide-based inorganic solid electrolyte material measured under the conditions of a temperature of 25° C., a sweep voltage range of 0 to 5 V, and a voltage sweep rate of 5 mV / sec is preferably 0.50 μA or less, more preferably 0.20 μA or less, even more preferably 0.10 μA or less, even more preferably 0.05 μA or less, and particularly preferably 0.03 μA or less. It is preferable that the maximum value of the oxidative decomposition current of the sulfide-based inorganic solid electrolyte material is equal to or less than the above upper limit value, since the oxidative decomposition of the sulfide-based inorganic solid electrolyte material in the lithium ion battery can be suppressed. The lower limit of the maximum value of the oxidative decomposition current of the sulfide-based inorganic solid electrolyte material is not particularly limited, but is, for example, 0.0001 μA or more.

[0038] The sulfide-based inorganic solid electrolyte material according to this embodiment can be used in any application requiring lithium ion conductivity. In particular, the sulfide-based inorganic solid electrolyte material according to this embodiment is preferably used in a lithium ion battery. More specifically, it is used in a positive electrode active material layer, a negative electrode active material layer, an electrolyte layer, etc. in a lithium ion battery. Furthermore, the sulfide-based inorganic solid electrolyte material according to this embodiment is preferably used in a positive electrode active material layer, a negative electrode active material layer, a solid electrolyte layer, etc. constituting an all-solid-state lithium ion battery, and is particularly preferably used in a solid electrolyte layer constituting an all-solid-state lithium ion battery. An example of an all-solid-state lithium ion battery using the sulfide-based inorganic solid electrolyte material according to this embodiment is one in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order.

[0039] [Method of manufacturing sulfide-based inorganic solid electrolyte material] Next, a method for producing the sulfide-based inorganic solid electrolyte material according to this embodiment will be described. The method for producing the sulfide-based inorganic solid electrolyte material according to this embodiment includes, for example, a step of mechanically treating a raw material composition for the sulfide-based inorganic solid electrolyte material, which contains the phosphorus sulfide composition according to this embodiment and lithium sulfide. More specifically, the sulfide-based inorganic solid electrolyte material according to this embodiment can be obtained, for example, by a manufacturing method including the following steps (A) and (B). In addition, the manufacturing method of the sulfide-based inorganic solid electrolyte material according to this embodiment may further include the following steps (C) and (D) as necessary. Step (A): A step of preparing a raw material composition for a sulfide-based inorganic solid electrolyte material containing the phosphorus sulfide composition according to this embodiment and lithium sulfide. Step (B): A step of mechanically treating the raw material composition of the sulfide-based inorganic solid electrolyte material to chemically react and vitrify the raw materials, the phosphorus sulfide composition and lithium sulfide, to obtain a sulfide-based inorganic solid electrolyte material in a glassy state. Step (C) Heating the obtained sulfide-based inorganic solid electrolyte material in a glass state to crystallize at least a portion of it. Step (D): A step of pulverizing, classifying, or granulating the obtained sulfide-based inorganic solid electrolyte material.

[0040] (Step (A) of Preparing a Raw Material Composition of a Sulfide-Based Inorganic Solid Electrolyte Material) First, a raw material composition for a sulfide-based inorganic solid electrolyte material is prepared, which contains the phosphorus sulfide composition according to the present embodiment as a raw material, lithium sulfide, and further contains lithium nitride as necessary. Here, the mixing ratio of each raw material in the raw material composition is adjusted so that the resulting sulfide-based inorganic solid electrolyte material has a desired composition ratio. The method for mixing the raw materials is not particularly limited as long as it can mix the raw materials uniformly. For example, the raw materials can be mixed using a ball mill, a bead mill, a vibration mill, an impact crusher, a mixer (a pug mixer, a ribbon mixer, a tumbler mixer, a drum mixer, a V-type mixer, etc.), a kneader, a two-shaft kneader, an airflow crusher, a crusher, a rotary blade crusher, etc. The mixing conditions when mixing the raw materials, such as the stirring speed, processing time, temperature, reaction pressure, and gravitational acceleration applied to the mixture, can be appropriately determined depending on the processing amount of the mixture.

[0041] The lithium sulfide used as the raw material is not particularly limited, and commercially available lithium sulfide may be used, or lithium sulfide obtained by reacting lithium hydroxide with hydrogen sulfide may be used. From the viewpoint of obtaining a high-purity sulfide-based inorganic solid electrolyte material and suppressing side reactions, it is preferable to use lithium sulfide with few impurities. In this embodiment, lithium sulfide also includes lithium polysulfide.

[0042] Lithium nitride may be used as the raw material. Here, since the nitrogen in lithium nitride is discharged into the system as N2, by using lithium nitride as the raw inorganic compound, it becomes possible to increase only the Li composition in a sulfide-based inorganic solid electrolyte material that contains Li, P, and S as constituent elements. The lithium nitride according to the present embodiment is not particularly limited, and may be commercially available lithium nitride (e.g., Li3N, etc.), or may be obtained by reacting metallic lithium (e.g., Li foil) with nitrogen gas. From the viewpoint of obtaining a high-purity solid electrolyte material and suppressing side reactions, it is preferable to use lithium nitride with few impurities.

[0043] (Step (B) of obtaining a sulfide-based inorganic solid electrolyte material in a glassy state) Next, the raw material composition of the sulfide-based inorganic solid electrolyte material is mechanically treated to vitrify the raw materials, the phosphorus sulfide composition and lithium sulfide, while causing a chemical reaction therebetween, thereby obtaining a sulfide-based inorganic solid electrolyte material in a glassy state.

[0044] Here, the mechanical treatment is a method of mechanically colliding two or more inorganic compounds to cause a chemical reaction and vitrification, such as mechanochemical treatment, etc. Here, the mechanochemical treatment is a method of vitrification by applying mechanical energy such as shear force or collision force to the target composition. In the step (B), the mechanochemical treatment is preferably a dry mechanochemical treatment, from the viewpoint of easily realizing an environment in which moisture and oxygen are removed to a high degree. By using the mechanochemical treatment, the raw materials can be mixed while being pulverized into fine particles, so that the contact area of ​​the raw materials can be increased, thereby accelerating the reaction of the raw materials, and the sulfide-based inorganic solid electrolyte material according to the present embodiment can be obtained more efficiently.

[0045] Here, mechanochemical treatment is a method of vitrification while applying mechanical energy such as shear force, impact force, or centrifugal force to the mixture. Examples of devices for vitrification by mechanochemical treatment (hereinafter referred to as vitrification devices) include crushing and dispersing machines such as ball mills, bead mills, vibration mills, turbo mills, mechanofusion, disk mills, and roll mills; rotary and impact crushing devices consisting of a mechanism combining rotation (shear stress) and impact (compression stress), such as rock drills, vibration drills, and impact drivers; high-pressure grinding rolls; and vertical mills such as roller-type vertical mills and ball-type vertical mills. Among these, ball mills and bead mills are preferred from the viewpoint of efficiently generating very high impact energy, and ball mills are particularly preferred. From the viewpoint of excellent continuous productivity, preferred are roll mills; rotary / impact crushing devices consisting of a mechanism combining rotation (shear stress) and impact (compressive stress), such as rock drills, vibration drills, and impact drivers; high-pressure gliding rolls; and vertical mills, such as roller-type vertical mills and ball-type vertical mills.

[0046] The mixing conditions such as the rotation speed, processing time, temperature, reaction pressure, and gravitational acceleration applied to the raw inorganic composition when mechanically processing the raw material composition of the sulfide-based inorganic solid electrolyte material can be appropriately determined depending on the type and processing amount of the raw inorganic composition. In general, the faster the rotation speed, the faster the glass production rate, and the longer the processing time, the higher the conversion rate to glass. Typically, when X-ray diffraction analysis is performed using CuKα radiation as a radiation source, if the diffraction peaks derived from the raw materials disappear or decrease, it can be determined that the raw material composition of the sulfide-based inorganic solid electrolyte material has been vitrified and the desired sulfide-based inorganic solid electrolyte material has been obtained.

[0047] In the step (B), the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material is preferably 1.0×10 or less when measured by an AC impedance method under the measurement conditions of 27.0° C., an applied voltage of 10 mV, and a measurement frequency range of 0.1 Hz to 7 MHz. -4 S cm -1 More preferably, 2.0×10-4 S cm -1 More preferably, 3.0×10 -4 S cm -1 More preferably, 4.0×10 -4 S cm -1 It is preferable to carry out the vitrification treatment until the temperature reaches or exceeds this level, whereby a sulfide-based inorganic solid electrolyte material having even more excellent lithium ion conductivity can be obtained.

[0048] (Step (C) of crystallizing at least a part of the sulfide-based inorganic solid electrolyte material) Next, the obtained sulfide-based inorganic solid electrolyte material in a glass state is heated to crystallize at least a portion of the sulfide-based inorganic solid electrolyte material, thereby producing a sulfide-based inorganic solid electrolyte material in a glass ceramic state (also called crystallized glass). In this way, a sulfide-based inorganic solid electrolyte material having even better lithium ion conductivity can be obtained. That is, the sulfide-based inorganic solid electrolyte material according to this embodiment is preferably in a glass ceramic state (crystallized glass state) because it has excellent lithium ion conductivity.

[0049] The temperature at which the sulfide-based inorganic solid electrolyte material in a glassy state is heated is preferably within the range of 220°C or higher and 500°C or lower, and more preferably within the range of 250°C or higher and 350°C or lower. The time for heating the sulfide-based inorganic solid electrolyte material in a glass state is not particularly limited as long as it is a time that can obtain a sulfide-based inorganic solid electrolyte material in a desired glass ceramic state, but is, for example, within the range of 0.5 hours to 24 hours, preferably 1 hour to 3 hours. The heating method is not particularly limited, but for example, a method using a baking furnace can be mentioned. The conditions such as temperature and time during such heating can be appropriately adjusted to optimize the properties of the sulfide-based inorganic solid electrolyte material according to this embodiment.

[0050] In addition, the sulfide-based inorganic solid electrolyte material in a glassy state is preferably heated, for example, in an inert gas atmosphere, which can prevent deterioration (for example, oxidation) of the sulfide-based inorganic solid electrolyte material. Examples of inert gases used when heating the sulfide-based inorganic solid electrolyte material in a glassy state include argon gas, helium gas, and nitrogen gas. These inert gases are preferably as pure as possible to prevent impurities from being mixed into the product, and the dew point is preferably -30°C or less, more preferably -70°C or less, and particularly preferably -80°C or less to avoid contact with moisture. The method of introducing the inert gas into the mixed system is not particularly limited as long as the mixed system is filled with an inert gas atmosphere, and examples of the method include a method of purging the inert gas and a method of continuously introducing a constant amount of the inert gas.

[0051] (Process (D) of crushing, classifying, or granulating) In the method for producing a sulfide-based inorganic solid electrolyte material according to this embodiment, a step of pulverizing, classifying, or granulating the obtained sulfide-based inorganic solid electrolyte material may be further performed as necessary. For example, a sulfide-based inorganic solid electrolyte material having a desired particle size can be obtained by pulverizing to obtain fine particles, and then adjusting the particle size by a classification operation or a granulation operation. The above-mentioned pulverizing method is not particularly limited, and known pulverizing methods such as a mixer, airflow pulverization, a mortar, a rotary mill, and a coffee mill can be used. The above-mentioned classification method is also not particularly limited, and known methods such as a sieve can be used. The pulverization or classification is preferably carried out in an inert gas atmosphere or a vacuum atmosphere, since this can prevent contact with moisture in the air.

[0052] In order to obtain the sulfide-based inorganic solid electrolyte material according to this embodiment, it is important to appropriately adjust each of the above steps. However, the method for producing the sulfide-based inorganic solid electrolyte material according to this embodiment is not limited to the above method, and the sulfide-based inorganic solid electrolyte material according to this embodiment can be obtained by appropriately adjusting various conditions.

[0053] [Solid electrolyte] Next, the solid electrolyte according to the present embodiment will be described. The solid electrolyte according to the present embodiment includes the sulfide-based inorganic solid electrolyte material according to the present embodiment. The solid electrolyte according to the present embodiment is not particularly limited, but may contain, as a component other than the sulfide-based inorganic solid electrolyte material according to the present embodiment, for example, a solid electrolyte material of a type different from the sulfide-based inorganic solid electrolyte material according to the present embodiment described above, within a range that does not impair the object of the present invention.

[0054] The solid electrolyte according to the present embodiment may contain a solid electrolyte material different from the sulfide-based inorganic solid electrolyte material according to the present embodiment. The solid electrolyte material different from the sulfide-based inorganic solid electrolyte material according to the present embodiment is not particularly limited as long as it has ion conductivity and insulating properties, but can be one generally used in lithium ion batteries. For example, inorganic solid electrolyte materials such as sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials different from the sulfide-based inorganic solid electrolyte material according to the present embodiment; organic solid electrolyte materials such as polymer electrolytes can be mentioned.

[0055] As an example of a sulfide-based inorganic solid electrolyte material different from the sulfide-based inorganic solid electrolyte material according to the present embodiment described above, Li2S-P4S 10 Material, Li2S-SiS2 material, Li2S-GeS2 material, Li2S-Al2S3 material, Li2S-SiS2-Li3PO4 material, Li2S-P4S 10 -GeS2 material, Li2S-Li2O-P4S 10 -SiS2 material, Li2S-GeS2-P4S 10 -SiS2 material, Li2S-SnS2-P4S 10 -SiS2 material, Li2S-P4S 10 -Li3N material, Li2S 2+X -P4S3 material, Li2S-P4S 10-Examples include P4S3 materials. These may be used alone or in combination of two or more. Among these, from the viewpoint of excellent lithium ion conductivity and stability without decomposition or the like in a wide voltage range, Li2S-P4S 10 materials are preferred. Here, for example, Li2S-P4S 10 materials refer to solid electrolyte materials obtained by chemically reacting at least Li2S (lithium sulfide) and P4S 10 with each other by mechanical treatment of an inorganic composition containing them. Here, in this embodiment, lithium sulfide includes polysulfide lithium.

[0056] Examples of the oxide-based inorganic solid electrolyte materials include NASICON types such as LiTi2(PO4)3, LiZr2(PO4)3, LiGe2(PO4)3, and perovskite types such as (La 0.5+x Li 0.5-3x )TiO3, Li2O-P2O5 materials, Li2O-P2O5-Li3N materials, and the like. Examples of other lithium-based inorganic solid electrolyte materials include LiPON, LiNbO3, LiTaO3, Li3PO4, LiPO 4-x N x (where x is 0 < x ≤ 1), LiN, LiI, LISICON, and the like. Furthermore, glass ceramics obtained by precipitating crystals of these inorganic solid electrolytes can also be used as inorganic solid electrolyte materials.

[0057] Examples of the organic solid electrolyte materials include polymer electrolytes such as dry polymer electrolytes and gel electrolytes. As the polymer electrolyte, those generally used in lithium ion batteries can be used.

[0058] [Solid electrolyte membrane] Next, the solid electrolyte membrane according to this embodiment will be described. The solid electrolyte membrane according to this embodiment contains, as a main component, a solid electrolyte containing the sulfide-based inorganic solid electrolyte material according to this embodiment described above.

[0059] The solid electrolyte membrane according to this embodiment is used, for example, as a solid electrolyte layer constituting an all-solid-state lithium ion battery. An example of an all-solid-state lithium ion battery using the solid electrolyte membrane according to this embodiment is one in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order, where the solid electrolyte layer is made of the solid electrolyte membrane.

[0060] The average thickness of the solid electrolyte membrane according to the present embodiment is preferably 5 μm or more and 500 μm or less, more preferably 10 μm or more and 200 μm or less, and even more preferably 20 μm or more and 100 μm or less. When the average thickness of the solid electrolyte membrane is equal to or more than the lower limit, the loss of the solid electrolyte and the occurrence of cracks on the surface of the solid electrolyte membrane can be further suppressed. When the average thickness of the solid electrolyte membrane is equal to or less than the upper limit, the impedance of the solid electrolyte membrane can be further reduced. As a result, the battery characteristics of the obtained all-solid-state lithium ion battery can be further improved.

[0061] The solid electrolyte membrane according to the present embodiment is preferably a pressure-molded body of a particulate solid electrolyte containing the sulfide-based inorganic solid electrolyte material according to the present embodiment described above. That is, it is preferable to pressurize the particulate solid electrolyte to form a solid electrolyte membrane having a certain strength by the anchor effect between the solid electrolyte materials. By forming the solid electrolyte into a pressure-molded body, the solid electrolyte particles bond together, and the strength of the resulting solid electrolyte membrane is further increased, which further suppresses chipping of the solid electrolyte and the occurrence of cracks on the surface of the solid electrolyte membrane.

[0062] The content of the sulfide-based inorganic solid electrolyte material according to the present embodiment in the solid electrolyte membrane according to the present embodiment is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, when the entire solid electrolyte membrane is taken as 100% by mass. This improves the contact between the solid electrolytes, and reduces the interface contact resistance of the solid electrolyte membrane. As a result, the lithium ion conductivity of the solid electrolyte membrane can be further improved. And, by using such a solid electrolyte membrane having excellent lithium ion conductivity, the battery characteristics of the obtained all-solid-state lithium ion battery can be further improved. The upper limit of the content of the sulfide-based inorganic solid electrolyte material according to the present embodiment in the solid electrolyte membrane according to the present embodiment is not particularly limited, but is, for example, 100 mass % or less.

[0063] The planar shape of the solid electrolyte membrane is not particularly limited and can be appropriately selected in accordance with the shapes of the electrodes and current collectors, but can be, for example, rectangular.

[0064] The solid electrolyte membrane according to the present embodiment may contain a binder resin, but the content of the binder resin is preferably less than 0.5 mass%, more preferably 0.1 mass% or less, even more preferably 0.05 mass% or less, and even more preferably 0.01 mass% or less, when the entire solid electrolyte membrane is taken as 100 mass%. It is even more preferable that the solid electrolyte membrane according to the present embodiment does not substantially contain a binder resin, and it is most preferable that the solid electrolyte membrane does not contain a binder resin. This improves the contact between the solid electrolytes, and reduces the interface contact resistance of the solid electrolyte film. As a result, the lithium ion conductivity of the solid electrolyte film can be further improved. By using such a solid electrolyte film with excellent lithium ion conductivity, the battery characteristics of the obtained all-solid-state lithium ion battery can be improved. In addition, "substantially free of binder resin" means that the binder resin may be contained to the extent that the effect of the present embodiment is not impaired. In addition, when an adhesive resin layer is provided between the solid electrolyte layer and the positive electrode or the negative electrode, the adhesive resin originating from the adhesive resin layer present in the vicinity of the interface between the solid electrolyte layer and the adhesive resin layer is excluded from the "binder resin in the solid electrolyte membrane."

[0065] The binder resin mentioned above refers to a binder that is generally used in lithium ion batteries to bind inorganic solid electrolyte materials together. Examples of such binder resins include polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, and polyimide.

[0066] The solid electrolyte membrane according to this embodiment can be obtained, for example, by depositing particulate solid electrolyte into a film on a cavity surface of a mold or on a substrate surface, and then pressurizing the solid electrolyte deposited in the film form. The method for pressurizing the solid electrolyte is not particularly limited. For example, when a particulate solid electrolyte is deposited on the cavity surface of a mold, pressing with a mold and a stamping die can be used. When a particulate solid electrolyte is deposited on the surface of a substrate, pressing with a mold and a stamping die, roll pressing, flat plate pressing, or the like can be used. The pressure applied to the solid electrolyte is, for example, 10 MPa or more and 500 MPa or less.

[0067] If necessary, the inorganic solid electrolyte deposited in the form of a film may be heated while being pressurized. Heating and pressurization causes fusion and bonding of the solid electrolytes, and the strength of the resulting solid electrolyte film is further increased. As a result, loss of the solid electrolyte and the occurrence of cracks on the surface of the solid electrolyte film can be further suppressed. The temperature to which the solid electrolyte is heated is, for example, 40° C. or higher and 500° C. or lower.

[0068] [Lithium-ion battery] FIG. 1 is a cross-sectional view showing an example of the structure of a lithium-ion battery 100 according to an embodiment of the present invention. The lithium ion battery 100 according to this embodiment includes, for example, a positive electrode 110 including a positive electrode active material layer 101, an electrolyte layer 120, and a negative electrode 130 including a negative electrode active material layer 103. At least one of the positive electrode active material layer 101, the negative electrode active material layer 103, and the electrolyte layer 120 contains the sulfide-based inorganic solid electrolyte material according to this embodiment. It is preferable that all of the positive electrode active material layer 101, the negative electrode active material layer 103, and the electrolyte layer 120 contain the sulfide-based inorganic solid electrolyte material according to this embodiment. In this embodiment, unless otherwise specified, the layer including the positive electrode active material is called the positive electrode active material layer 101. The positive electrode 110 may further include a current collector 105 in addition to the positive electrode active material layer 101 as necessary, or may not include the current collector 105. In this embodiment, unless otherwise specified, the layer including the negative electrode active material is called the negative electrode active material layer 103. The negative electrode 130 may further include a current collector 105 in addition to the negative electrode active material layer 103, as necessary, or may not include the current collector 105. The shape of the lithium ion battery 100 according to this embodiment is not particularly limited, and examples thereof include a cylindrical shape, a coin shape, a square shape, a film shape, and any other shape.

[0069] The lithium ion battery 100 according to this embodiment is manufactured according to a generally known method, for example, by forming a stack of the positive electrode 110, the electrolyte layer 120, and the negative electrode 130 into a cylindrical, coin, square, film, or other arbitrary shape, and sealing a nonaqueous electrolyte solution therein as necessary.

[0070] (positive electrode) The positive electrode 110 is not particularly limited, and any electrode generally used in lithium ion batteries can be used. The positive electrode 110 is not particularly limited, and can be manufactured according to a generally known method. For example, the positive electrode 110 can be obtained by forming a positive electrode active material layer 101 containing a positive electrode active material on the surface of a current collector 105 such as aluminum foil. The thickness and density of the positive electrode active material layer 101 are appropriately determined depending on the intended use of the battery, and are not particularly limited, and can be set in accordance with generally known information.

[0071] The positive electrode active material layer 101 contains a positive electrode active material. The positive electrode active material is not particularly limited, and generally known materials can be used. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), solid solution oxide (Li2MnO3-LiMO2 (M=Co, Ni, etc.)), lithium-manganese-nickel oxide (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2), composite oxides such as olivine-type lithium phosphate oxide (LiFePO4); conductive polymers such as polyaniline and polypyrrole; sulfide-based positive electrode active materials such as Li2S, CuS, Li-Cu-S compounds, TiS2, FeS, MoS2, Li-Mo-S compounds, Li-Ti-S compounds, Li-VS compounds, and Li-Fe-S compounds; materials using sulfur as an active material such as sulfur-impregnated acetylene black, sulfur-impregnated porous carbon, and mixed powder of sulfur and carbon; and the like can be used. These positive electrode active materials may be used alone or in combination of two or more. Among these, from the viewpoint of having a higher discharge capacity density and superior cycle characteristics, a sulfide-based positive electrode active material is preferred, and one or more selected from a Li-Mo-S compound, a Li-Ti-S compound, and a Li-VS compound are more preferred.

[0072] Here, the Li-Mo-S compound contains Li, Mo, and S as constituent elements, and can usually be obtained by chemically reacting the raw materials, molybdenum sulfide and an inorganic composition containing lithium sulfide, with each other through a mechanical treatment. In addition, the Li-Ti-S compound contains Li, Ti, and S as constituent elements, and can usually be obtained by chemically reacting inorganic compositions containing titanium sulfide and lithium sulfide, which are raw materials, with each other through mechanical processing. Li-VS compounds contain the constituent elements Li, V, and S, and are usually obtained by chemically reacting the raw materials vanadium sulfide and lithium sulfide with each other through mechanical processing.

[0073] The positive electrode active material layer 101 is not particularly limited, and may contain, as a component other than the positive electrode active material, for example, one or more materials selected from a binder resin, a thickener, a conductive assistant, a solid electrolyte material, etc. Each material will be described below.

[0074] The positive electrode active material layer 101 may contain a binder resin that serves to bind the positive electrode active materials together and between the positive electrode active material and the current collector 105 . The binder resin according to the present embodiment is not particularly limited as long as it is a typical binder resin that can be used in lithium ion batteries, and examples thereof include polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyimide, etc. These binders may be used alone or in combination of two or more.

[0075] The positive electrode active material layer 101 may contain a thickener in order to ensure the fluidity of the slurry suitable for application. The thickener is not particularly limited as long as it is a normal thickener that can be used in lithium ion batteries, and examples thereof include cellulose-based polymers such as carboxymethyl cellulose, methyl cellulose, and hydroxypropyl cellulose, and ammonium salts and alkali metal salts thereof, water-soluble polymers such as polycarboxylic acid, polyethylene oxide, polyvinylpyrrolidone, polyacrylate, and polyvinyl alcohol. These thickeners may be used alone or in combination of two or more.

[0076] The positive electrode active material layer 101 may contain a conductive assistant from the viewpoint of improving the conductivity of the positive electrode 110. The conductive assistant is not particularly limited as long as it is a normal conductive assistant that can be used in lithium ion batteries, and examples of the conductive assistant include carbon black such as acetylene black and ketjen black, and carbon materials such as vapor-grown carbon fiber.

[0077] The positive electrode according to the present embodiment may contain a solid electrolyte containing the sulfide-based inorganic solid electrolyte material according to the present embodiment described above, or may contain a solid electrolyte containing a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material according to the present embodiment. The solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material according to the present embodiment is not particularly limited as long as it has ion conductivity and insulating properties, but can be one generally used in lithium ion batteries. For example, inorganic solid electrolyte materials such as sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials; organic solid electrolyte materials such as polymer electrolytes can be mentioned. More specifically, the inorganic solid electrolyte materials mentioned in the description of the solid electrolyte according to the present embodiment can be used.

[0078] The blending ratio of the various materials in the positive electrode active material layer 101 is appropriately determined depending on the intended use of the battery, and is not particularly limited, and can be set in accordance with generally known information.

[0079] (Negative electrode) The negative electrode 130 is not particularly limited, and any electrode generally used in lithium ion batteries can be used. The negative electrode 130 is not particularly limited, and can be manufactured according to a generally known method. For example, the negative electrode 130 can be obtained by forming a negative electrode active material layer 103 containing a negative electrode active material on the surface of a current collector 105 such as copper. The thickness and density of the negative electrode active material layer 103 are not particularly limited since they are appropriately determined depending on the intended use of the battery, and can be set in accordance with generally known information.

[0080] The negative electrode active material layer 103 contains a negative electrode active material. The negative electrode active material is not particularly limited as long as it is a normal negative electrode active material that can be used for the negative electrode of a lithium ion battery. Examples of the negative electrode active material include carbonaceous materials such as natural graphite, artificial graphite, resin carbon, carbon fiber, activated carbon, hard carbon, and soft carbon; metallic materials mainly composed of lithium, lithium alloys, tin, tin alloys, silicon, silicon alloys, gallium, gallium alloys, indium, indium alloys, aluminum, and aluminum alloys; conductive polymers such as polyacene, polyacetylene, and polypyrrole; and lithium titanium composite oxides (e.g., Li4Ti5O 12 These negative electrode active materials may be used alone or in combination of two or more.

[0081] The negative electrode active material layer 103 is not particularly limited, but may contain, as a component other than the negative electrode active material, one or more materials selected from, for example, a binder resin, a thickener, a conductive assistant, a solid electrolyte material, etc. These materials are not particularly limited, but may be, for example, the same materials as those used for the positive electrode 110 described above. The blending ratio of the various materials in the negative electrode active material layer 103 is appropriately determined depending on the intended use of the battery, and is not particularly limited, and can be set in accordance with generally known information.

[0082] (electrolyte layer) Next, a description will be given of the electrolyte layer 120. The electrolyte layer 120 is a layer formed between the positive electrode active material layer 101 and the negative electrode active material layer 103. The electrolyte layer 120 may be a separator impregnated with a non-aqueous electrolyte solution or a solid electrolyte layer containing a solid electrolyte.

[0083] The separator according to this embodiment is not particularly limited as long as it electrically insulates the positive electrode 110 and the negative electrode 130 and allows lithium ions to pass through, and for example, a porous membrane can be used.

[0084] As the porous membrane, a microporous polymer film is preferably used, and examples of the material include polyolefin, polyimide, polyvinylidene fluoride, polyester, etc. In particular, a porous polyolefin film is preferable, and specific examples thereof include a porous polyethylene film, a porous polypropylene film, etc.

[0085] The non-aqueous electrolyte is a solution in which an electrolyte is dissolved in a solvent. Any known lithium salt can be used as the electrolyte, and may be selected according to the type of active material. For example, LiClO4, LiBF6, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiB 10 Cl 10 , LiAlCl4, LiCl, LiBr, LiB(C2H5)4, CF3SO3Li, CH3SO3Li, LiCF3SO3, LiC4F9SO3, Li(CF3SO2)2N, and lithium lower fatty acid carboxylates.

[0086] The solvent for dissolving the electrolyte is not particularly limited as long as it is a solvent that is usually used as a liquid for dissolving electrolytes, and examples of the solvent include carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), and vinylene carbonate (VC); lactones such as γ-butyrolactone and γ-valerolactone; ethers such as trimethoxymethane, 1,2-dimethoxyethane, diethyl ether, 2-ethoxyethane, tetrahydrofuran, and 2-methyltetrahydrofuran; Examples of such compounds include sulfoxides such as dimethyl sulfoxide, oxolanes such as 1,3-dioxolane and 4-methyl-1,3-dioxolane, nitrogen-containing compounds such as acetonitrile, nitromethane, formamide, and dimethylformamide, organic acid esters such as methyl formate, methyl acetate, ethyl acetate, butyl acetate, methyl propionate, and ethyl propionate, phosphoric acid triesters and diglymes, triglymes, sulfolanes such as sulfolane and methyl sulfolane, oxazolidinones such as 3-methyl-2-oxazolidinone, and sultones such as 1,3-propane sultone, 1,4-butane sultone, and naphtha sultone. These compounds may be used alone or in combination of two or more.

[0087] The solid electrolyte layer according to this embodiment is a layer formed between the positive electrode active material layer 101 and the negative electrode active material layer 103, and is a layer formed of a solid electrolyte containing a solid electrolyte material. The solid electrolyte contained in the solid electrolyte layer is not particularly limited as long as it has lithium ion conductivity, but in this embodiment, it is preferable that the solid electrolyte contains the sulfide-based inorganic solid electrolyte material according to this embodiment. The content of the solid electrolyte in the solid electrolyte layer according to the present embodiment is not particularly limited as long as the desired insulating properties can be obtained, but is preferably, for example, in the range of 10% by volume or more and 100% by volume or less, and more preferably, in the range of 50% by volume or more and 100% by volume or less. In particular, in the present embodiment, it is preferable that the solid electrolyte layer is composed only of a solid electrolyte containing the sulfide-based inorganic solid electrolyte material according to the present embodiment.

[0088] The solid electrolyte layer according to the present embodiment may contain a binder resin. By containing the binder resin, a flexible solid electrolyte layer can be obtained. Examples of the binder resin include fluorine-containing binders such as polytetrafluoroethylene and polyvinylidene fluoride. The thickness of the solid electrolyte layer is preferably in the range of 0.1 μm to 1000 μm, and more preferably in the range of 0.1 μm to 300 μm.

[0089] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. The present invention is not limited to the above-described embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. EXAMPLES

[0090] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.

[0091] [1]Measurement method First, the measurement methods used in the following Examples and Comparative Examples will be described.

[0092] (1) Particle size distribution The particle size distribution of the sulfide-based inorganic solid electrolyte material obtained in the examples and comparative examples was measured by a laser diffraction method using a laser diffraction scattering type particle size distribution measuring device (Malvern Instruments, Mastersizer 3000). From the measurement results, the particle size (d 50 , average particle size) were calculated.

[0093] (2) solid 31 P-NMR measurement The phosphorus sulfide compositions obtained in the Examples and Comparative Examples were subjected to the following solid 31 P-NMR measurements were carried out for each. First, a test sample was loaded into a 3.2 mm diameter measurement sample tube in a glove box purged with N2 gas, and the tube was rotated at a magic angle (54.7 degrees) relative to the external magnetic field (Magic Angle Spinning: MAS), and measurements were performed under the following conditions. Equipment: JNM-ECA-600 manufactured by JEOL RESONANCE Co., Ltd. Observation frequency: 242.95MHz Pulse width: 90° pulse Pulse waiting time: 2800 seconds Number of times accumulated: 64 Measurement mode: Single pulse method MAS speed: 12kHz Standard substance: (NH4)2HPO4·1.33ppm Test sample 31 Regarding the peaks detected in the P-NMR spectrum, see Reference 1 "Hellmut Eckert, Cheryl S. Liang and Galen D. Stucky: 31 P magic angle spinning NMR of crystalline phosphorous sulfides. Correlation of 31P chemical shielding tensors with local environments, J. Phys. Chem, 1989, 93, 452-457, and waveform separation was performed using a Gaussian function based on the following peak assignments, and the integral value of each peak was calculated. The content ratio was calculated from the obtained integral value and the molecular weight of each component. P4S 10 The chemical shifts of P4S1, P4S2, and P4S3 are 40-52 ppm, 52-70 ppm, 80-90 ppm, 90-100 ppm, and 110-115 ppm, respectively, and P4S3, P4S4, and P4S5 are 80-90 ppm and 90-100 ppm, respectively.

[0094] (3) Measurement of the composition ratio of sulfide-based inorganic solid electrolyte materials Using an ICP optical emission spectrometer (Seiko Instruments Inc., SPS3000), measurements were performed by ICP optical emission spectroscopic analysis to determine the mass percentages of Li, P, and S in the sulfide-based inorganic solid electrolyte materials obtained in the examples and comparative examples, and the molar ratios of each element were calculated based on the results.

[0095] (4) Measurement of lithium ion conductivity The lithium ion conductivity of the sulfide-based inorganic solid electrolyte materials obtained in the examples and comparative examples was measured by an AC impedance method. The lithium ion conductivity was measured using a potentiostat / galvanostat SP-300 manufactured by Biologic Corp. The sample size was 9.5 mm in diameter and 1.2 to 2.0 mm in thickness, and the measurement conditions were an applied voltage of 10 mV, a measurement temperature of 27.0°C, a measurement frequency range of 0.1 Hz to 7 MHz, and a Li foil electrode. Here, as the sample for measuring lithium ion conductivity, a plate-shaped sulfide-based inorganic solid electrolyte material having a diameter of 9.5 mm and a thickness of 1.2 to 2.0 mm was used, which was obtained by pressing 150 mg of the powdered sulfide-based inorganic solid electrolyte material obtained in the examples and comparative examples at 270 MPa for 10 minutes using a pressing device.

[0096] [2] Manufacturing of solid electrolyte materials A sulfide-based inorganic solid electrolyte material was prepared by the following procedure. The raw materials used were Li2S (manufactured by Furukawa Co., Ltd., purity 99.9%) and Li3N (manufactured by Furukawa Co., Ltd.), and the phosphorus sulfide compositions obtained in the examples and comparative examples were used as phosphorus sulfide. First, a rotary blade grinder and an alumina pot (internal volume 400 mL) were placed in the glove box, and then high-purity dry argon gas (H2O<1 ppm, O2<1 ppm) obtained through a gas purification system was injected into the glove box and vacuum degassed three times. Next, in a glove box, a rotary blade grinder (rotation speed 18,000 rpm) was used to mix a total of 5 g of Li2S powder, phosphorus sulfide composition, and Li3N powder (Li2S:phosphorus sulfide composition:Li3N = 71.1:23.7:5.3 (mol%)) (10 times of mixing for 10 seconds and leaving for 10 seconds (cumulative mixing time: 100 seconds)), to prepare a raw material inorganic composition.

[0097] Next, the raw material inorganic composition and 500 g of ZrO2 balls having a diameter of 10 mm were placed in an alumina pot (inner volume: 400 mL) in the glove box, and the pot was sealed. Next, the alumina pot was taken out of the glove box, and the alumina pot was attached to a ball mill placed in an atmosphere of dry air introduced through a membrane air dryer, and mechanochemical treatment was carried out at 120 rpm for 500 hours to vitrify the raw material inorganic composition. After every 48 hours of mixing, the powder on the inner wall of the pot was scraped off in the glove box, and after sealing, milling was continued in a dry air atmosphere. Next, an alumina pot was placed in the glove box, and the obtained powder was transferred from the alumina pot to a carbon crucible, and annealed at 290° C. for 2 hours in a heating furnace installed in the glove box. The obtained sulfide-based inorganic solid electrolyte material was evaluated. The results are shown in Table 1.

[0098] [3] Production of phosphorus sulfide composition <Example 1> As phosphorus sulfide raw material composition 1, diphosphorus pentasulfide (product name: SUPERIOR GRADE Powder) manufactured by LIAONING RUIXING CHEMICAL GROUP was used. Next, phosphorus sulfide raw material composition 1 was placed in a quartz container and set in a vacuum heating device (manufactured by Furukawa Co., Ltd.). Next, it was vacuum heated at 300°C for 2 hours under a reduced pressure of -0.094 MPa. Next, the components that had accumulated at the bottom of the quartz container were collected to obtain phosphorus sulfide composition 1. The obtained phosphorus sulfide composition 1 was subjected to various evaluations. The obtained results are shown in Table 1.

[0099] <Example 2> As phosphorus sulfide raw material composition 2, diphosphorus pentasulfide (product name: Normal S) manufactured by Perimeter Solutions was used. Next, phosphorus sulfide raw material composition 2 was placed in a quartz container and set in a vacuum heating device (manufactured by Furukawa Co., Ltd.). Next, it was vacuum heated at 300°C for 2 hours under a reduced pressure of -0.094 MPa. Next, the components that had accumulated at the bottom of the quartz container were collected to obtain phosphorus sulfide composition 2. The obtained phosphorus sulfide composition 2 was subjected to various evaluations. The obtained results are shown in Table 1.

[0100] <Example 3> As phosphorus sulfide raw material composition 3, diphosphorus pentasulfide (product name: Special S) manufactured by Perimeter Solutions was used. Next, the phosphorus sulfide raw material composition was placed in a quartz container and set in a vacuum heating device (manufactured by Furukawa Co., Ltd.). Next, it was vacuum heated at 300°C for 2 hours under a reduced pressure of -0.094 MPa. Next, the components that had accumulated at the bottom of the quartz container were collected to obtain phosphorus sulfide composition 3. The obtained phosphorus sulfide composition 3 was subjected to various evaluations. The obtained results are shown in Table 1.

[0101] <Comparative Example 1> Diphosphorus pentasulfide (product name: SUPERIOR GRADE Powder) manufactured by LIAONING RUIXING CHEMICAL GROUP was used as it was as phosphorus sulfide composition 4. Various evaluations were performed on phosphorus sulfide composition 4. The obtained results are shown in Table 1.

[0102] <Comparative Example 2> Diphosphorus pentasulfide (product name: Special S) manufactured by Perimeter Solutions was used as is as phosphorus sulfide composition 5. Various evaluations were performed on phosphorus sulfide composition 5. The obtained results are shown in Table 1.

[0103] The phosphorus sulfide raw material composition manufactured by LIAONING RUIXING CHEMICAL GROUP and the phosphorus sulfide raw material composition manufactured by Perimeter Solutions, which were used in the examples and comparative examples, are both commercially available as high purity grades.

[0104] [Table 1]

[0105] The sulfide-based inorganic solid electrolyte material obtained using the phosphorus sulfide composition of the Example as a raw material had superior lithium ion conductivity to the sulfide-based inorganic solid electrolyte material obtained using the phosphorus sulfide composition of the Comparative Example as a raw material.

[0106] This application claims priority based on Japanese Patent Application No. 2019-182305, filed on October 2, 2019, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]

[0107] 100 Lithium-ion batteries 101 Cathode active material layer 103 Negative electrode active material layer 105 Current collector 110 Positive electrode 120 Electrolyte layer 130 negative electrode

Claims

1. A phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, comprising: P 4 S 10 and P 4 S 9 Including, P in the phosphorus sulfide composition 4 S 10 , P 4 S 9 , P 4 S 7 and P 4 S 3 When the total content of is 100 mass%, solid 31 The P calculated from the P-NMR spectrum 4 S 10 The content is 70% by mass or more and 99% by mass or less, The phosphorus sulfide composition has a P 4 S 9 content of 1 mass % or more and 23 mass % or less (provided that the sulfide-based inorganic solid electrolyte material excludes a sulfide solid electrolyte material having an argyrodite-type crystal structure).

2. 2. The phosphorus sulfide composition of claim 1, solid 31 A phosphorus sulfide composition having no observed peak in the range of 80 ppm or more and 90 ppm or less when a P-NMR spectrum is measured.

3. 3. The phosphorus sulfide composition according to claim 1, P 4 S 10 and P 4 S 9 The phosphorus sulfide composition having a total content of 95 mass % or more.

4. The phosphorus sulfide composition according to any one of claims 1 to 3, A phosphorus sulfide composition in powder form.

5. A raw material composition for a sulfide-based inorganic solid electrolyte material, comprising the phosphorus sulfide composition according to claim 1 and lithium sulfide.

6. A method for producing a sulfide-based inorganic solid electrolyte material, comprising a step of mechanically treating the raw material composition for the sulfide-based inorganic solid electrolyte material according to claim 5.

7. A sulfide-based inorganic solid electrolyte material comprising a mechanically treated composition comprising the phosphorus sulfide composition according to claim 1 and lithium sulfide.

8. A solid electrolyte comprising the sulfide-based inorganic solid electrolyte material according to claim 7.

9. A solid electrolyte membrane comprising the solid electrolyte according to claim 8 as a main component.

10. A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, A lithium ion battery, wherein at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material according to claim 7.

Citation Information

Patent Citations

  • Sulfide solid electrolytic material, battery, and method for manufacturing sulfide solid electrolytic material

    JP2016027545A

  • Manufacturing method of solid electrolyte

    JP2016091717A

  • Sulfide glass and crystalline solid electrolyte production method, crystalline solid electrolyte, sulfide glass and solid-state battery

    WO2016067631A1

  • Method for producing sulfide solid electrolyte

    WO2018225526A1